Structural and optical properties of Eu3+ activated low cost zinc soda lime silica glasses - Sheh Omar, Nur Alia; Yap, Wing Fen; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz; Samsudin, Nur Farhana (Elsevier, 2016)
A low cost method was employed to synthesize ZnO-SLS:xEu3+ phosphors using recyclable bottle glass as silica source. The structural and optical properties of ZnO-SLS:xEu3+ (x = 0, 1, 2, 3, 4 and 5 wt.%) glasses were determined using X-ray diffraction (XRD), Fourier transform infrared reflectance (FTIR), UV-visible (Uv-Vis) and photoluminescence (PL) spectroscopy. Structural investigation using XRD measurement had broadened the halo peak with the doping of dopants. FTIR spectra showed the glass system consists of –OH and SiO4 bands. Meanwhile, the optical measurement using UV-Vis absorption has been induced a blue shift of the electronic absorption edge. The emission peak intensity of ZnO-SLS:xEu3+ phosphors was enhanced with the progression of doping concentration and thus, revealed their potential as red emitting phosphors under 400 nm excitation.